The Relationship Between Knowledge and Behavior in Preventing Acute Respiratory Infection (ARI) Among Students of SDN 017 Sekejati, Bandung City - Rukmasari, Ema Arum; Herman, Regina Yasmin; Solehati, Teti (International Journal of Science and Society, 2025)
Acute Respiratory Infection (ARI) is a major contributor to morbidity and mortality among children, particularly in developing countries such as Indonesia. Children are considered a vulnerable group, thus requiring a good understanding of how to prevent ARI. This study aimed to identify the relationship between knowledge level and preventive behavior toward ARI among students at SDN 017 Sekejati, Bandung City. The study employed a cross-sectional design with a total of 191 students from grades III to VI as respondents. Data were collected using a questionnaire and analyzed using the Chi-Square test and Cramér’s V. The Chi-Square test revealed a significant relationship between knowledge and ARI prevention behavior (χ² = 17.560; p < 0.001), with a Cramér’s V value of 0.3676, indicating a strong association. The findings conclude that the higher the students’ knowledge, the better their preventive actions against ARI. Continuous educational interventions are needed to enhance the effectiveness of health promotion efforts in elementary schools.